Analisis Faktor yang Berhubungan dengan Kejadian Hipertensi di Wilayah Kerja UPTD Puskesmas Ladang Tuha Desa Paya Ateuk - Masrita Herma; T. Alamsyah; Rubi Rimonda; Ernawati Ernawati; Rismawati Rismawati (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Introduction: Hypertension or high blood pressure is a disease characterized by an increase in blood pressure above normal that is progressive. Hypertension has become a world health problem due to its high prevalence and risk of causing heart, stroke, and kidney complications. The purpose of this study was to see if stress, smoking, diet and physical activity had a relationship with the incidence of hypertension in the working area of the UPTD Ladang Tuha Health Center, Paya Ateuk Village. Methods: This study uses a quantitative research design that uses an analytical descriptive method with a cross sectional approach. The population in this study is all heads of families in Paya Ateuk Village as many as 558 people. The sample selection technique used was purpose sampling which was determined by the slovin formula and obtained 85 samples. The collected data was then tested univariately to see the frequency distribution and bivariate using the chi-square (P-Value) test to see the influence between the variables. Results: The level of community stress was related to hypertension (p-value 0.000 < 0.05). Smoking habits also had a significant relationship (p-value 0.037 < 0.05). Diet was shown to be closely related to hypertension rates (p-value 0.000 < 0.05). Physical activity showed a significant correlation with hypertension (p-value 0.001 < 0.05). Conclusion: stress, smoking, diet and physical activity have a relationship with the occurrence of hypertension, this is supported by test results that get a P-value of less than 0.05.